Analisis Faktor Financial Behavior pada Mahasiswa Akuntansi - Saputri, Evieana Riesty; Erdi, Tio Waskito; Yuniarto, Andriono Eko (E-Jurnal Akuntansi; Vol 33 No 12 (2023)DO - 10.24843/EJA.2023.v33.i12.p11, 2023)
The aim of this research is to determine the factors that influence the financial behavior of accounting students. The population in this study were all students majoring in accounting in Yogyakarta Special Region Province, fourth semester and above. The sampling technique used was multistage random sampling so that a sample of 150 people was obtained. The test carried out using Smart-PLS is using the outer model and inner model. The research results show that financial literacy, parental involvement, self-efficacy, and overall social status influence the financial behavior of accounting students. Keywords: Financial Literacy; Parental Involvement; Self-efficacy; Social Status; Financial Behavior